2020
DOI: 10.1111/jog.14182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the plasma protein S dynamics during pregnancy using a total protein S assay: Protein S‐specific activity decreased from the second trimester

Abstract: Aim The relationship between congenital protein S (PS) deficiency and complications during pregnancy remains unclear, partly due to the difficulty of precisely evaluating the PS level with conventional assays and the physiological decrease of PS during pregnancy. A new PS assay was developed to measure the total PS antigen and activity quantitatively and calculate PS‐specific activity. This study aimed to evaluate the plasma PS dynamics during pregnancy using the new PS assay and establish the reference interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This result is consistent with those of previous studies showing a decline in protein S activity during pregnancy. Studies predominantly in Asian women showed a dramatic decrease in protein S activity from the first trimester, with no further decrease before delivery [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with those of previous studies showing a decline in protein S activity during pregnancy. Studies predominantly in Asian women showed a dramatic decrease in protein S activity from the first trimester, with no further decrease before delivery [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…PS activity was measured by a clotting method, and PS antigen levels were measured by a latex agglutination test. Because PS activity and antigen levels decrease during pregnancy and the postpartum period, 7) her blood tests were performed 6 months after the miscarriage. She was retested 1 year later and had the same levels.…”
Section: Case Reportmentioning
confidence: 99%